Unexpected Rupture of Ectopic Pregnancy with Shock: A Warning to Always Enhance Alertness - Eko Setyo Herwanto (Asian Journal of Health Research, 2024)
Introduction: Ectopic pregnancy (EP) describes a pregnancy that develops outside the uterine cavity. The fallopian tube, specifically the ampulla is the most common site. Positive blood β-hCG levels can identify EP with no ultrasound confirmation of intrauterine or extrauterine pregnancy. Case Presentation: We report a 37-year-old woman was referred from primary health care with a diagnosis of ileus. The patient complained of abdominal pain, spotting, vomiting, and no defecating since the day before; gestational age was estimated at around seven weeks. Vital signs indicated shock; the physical examination revealed slight abdominal distention, decreased bowel sounds, tenderness throughout the abdominal area, slightly defans muscular, and hyper tympanic. Vaginal touch didn't reveal cervical dilation, absent portio swaying pain. The laboratory found anemia and leukocytosis with a predominance of neutrophils. The pregnancy test was positive in the emergency department. Previously, the primary health care facility did not undergo a pregnancy test. Abdominal x-ray showed low-lying obstructive ileus and ascites in the pelvic cavity. Transabdominal ultrasound revealed free fluid in the rectouterine cavity. The patient underwent an emergency laparotomy, and a rupture in the ampulla segment was found, then a salpingectomy was performed. Conclusion: Clinicians must be able to diagnose EP correctly and as quickly as possible. In women of childbearing age presenting with acute abdominal complaints and a known or unknown history of menstruation, we strongly recommend a qualitative β-hCG examination, which can be carried out in health facilities with limited resources and at affordable costs, will be very useful for diagnosing and screening ectopic pregnancy.